Mechanical homeostasis imbalance in hepatic stellate cells activation and hepatic fibrosis - Zhao, Yuan-Quan; Deng, Xi-Wen; Xu, Guo-Qi; Lin, Jie; Lu, Hua-Ze; Chen, Jie (Frontiers in Molecular Biosciences, 2023)
Chronic liver disease or repeated damage to hepatocytes can give rise to hepatic fibrosis. Hepatic fibrosis is a pathological process of excessive sedimentation of extracellular matrix (ECM) proteins such as collagen, glycoproteins and proteoglycans in hepatic parenchyma. Changes in the composition of the ECM lead to the stiffness of the matrix that destroys its inherent mechanical homeostasis, and a mechanical homeostasis imbalance activates hepatic stellate cells (HSCs) into myofibroblasts, which can overproliferate and secrete large amounts of ECM proteins. Excessive ECM proteins are gradually deposited in the Disse gap, and matrix regeneration fails, which further leads to changes in ECM components and an increase in stiffness, forming a vicious cycle. These processes promote the occurrence and development of hepatic fibrosis. In this review, the dynamic process of ECM remodeling of hepatic fibrosis and the activation of HSCs into mechanotransduction signaling pathways for myofibroblasts to participate in hepatic fibrosis are discussed. These mechanotransduction signaling pathways may have potential therapeutic targets for repairing or reversing fibrosis.